Privilege, Economy and State in Old Regime France - Wade, Lewis (Boydell & Brewer, 2023)
This book closely analyses the rise and fall of Louis XIV's marine insurance institutions in Paris, which were central to the French monarchy's efforts to stimulate commerce, colonial enterprise and economic growth. These institutions were the projects of two leading ministers, Jean-Baptiste Colbert and his son, the Marquis de Seignelay. While both men recognised that marine insurance was crucial for protecting commercial investment in French maritime endeavours, Colbert looked to private enterprise to lure capital away from passive investments in state debt towards the marine insurance industry. Seignelay, by contrast, leveraged the tools of privilege on which the French economy was built by creating the first chartered company in the history of marine insurance. In exploring the global insurance portfolios of the men and women who joined these institutions - and the conflicts that arose when maritime incidents came into dispute - the book identifies the absolute monarchy itself as the source of the institutions' struggles. While the markets of Amsterdam and London thrived in the long run, Parisian insurers were made to bear the burden of maritime and colonial losses during Louis XIV's costly wars to make up for the state's inadequate protection of French shipping, the French Atlantic empire and the Parisian market. This encapsulates, the book argues, the overarching system of risk management that lay at the heart of absolutism itself. The ebook edition of this book is openly available under the Creative Commons license CC BY-NC-ND.